2003
DOI: 10.1111/1475-4754.00121
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Variations in Aged and Heated Pistacia Resin Found in Late Bronze Age Canaanite Amphorae and Bowls From Amarna, Egypt*

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 33 publications
3
76
0
2
Order By: Relevance
“…Dudd and Evershed 1998;Evershed et al 2002;Copley et al 2003;Evershed et al 2008;Dunne et al 2012;Debono Spiteri et al 2016). Likewise, aquatic products (Patrick et al 1985;Hansel et al 2004;Craig et al 2007;Hansel and Evershed 2009;Shoda et al 2017), plant oils and waxes denoting vegetable and plant oil consumption/ processing (Evershed et al 1991;Copley et al 2001a;Copley et al 2001b;Reber et al 2004;Copley et al 2005;Cramp et al 2011;Dunne et al 2016) and beeswax (Heron et al 1994;Charters et al 1995;Evershed et al 1997b;Regert et al 2001;Evershed et al 2003;Roffet-Salque et al 2015), resins, tars and bitumen (Beck et al 1989;Mills and White 1989;Evershed et al 1997a;van Bergen et al 1997;Urem-Kotsou et al 2002;Stern et al 2003;Buckley et al 2004;Stern et al 2008;Connan et al 2013;Brown et al 2014: Brettell et al 2014 have been identified in connection with a wide range of technological and cultural activities. On a broader scale, lipid residue analyses can provide insight into the domestication of plants and animals, the development of animal husbandry practices and ecological and environmental changes through time (Evershed 2008b;Evershed et al 2008;…”
Section: Introductionmentioning
confidence: 99%
“…Dudd and Evershed 1998;Evershed et al 2002;Copley et al 2003;Evershed et al 2008;Dunne et al 2012;Debono Spiteri et al 2016). Likewise, aquatic products (Patrick et al 1985;Hansel et al 2004;Craig et al 2007;Hansel and Evershed 2009;Shoda et al 2017), plant oils and waxes denoting vegetable and plant oil consumption/ processing (Evershed et al 1991;Copley et al 2001a;Copley et al 2001b;Reber et al 2004;Copley et al 2005;Cramp et al 2011;Dunne et al 2016) and beeswax (Heron et al 1994;Charters et al 1995;Evershed et al 1997b;Regert et al 2001;Evershed et al 2003;Roffet-Salque et al 2015), resins, tars and bitumen (Beck et al 1989;Mills and White 1989;Evershed et al 1997a;van Bergen et al 1997;Urem-Kotsou et al 2002;Stern et al 2003;Buckley et al 2004;Stern et al 2008;Connan et al 2013;Brown et al 2014: Brettell et al 2014 have been identified in connection with a wide range of technological and cultural activities. On a broader scale, lipid residue analyses can provide insight into the domestication of plants and animals, the development of animal husbandry practices and ecological and environmental changes through time (Evershed 2008b;Evershed et al 2008;…”
Section: Introductionmentioning
confidence: 99%
“…The presence of an unresolved complex mixture (a 'hump') around the retention time of the triterpenoids suggested there may have been a bitumen component of this balm; however, SIM analyses of the saturated hydrocarbon fraction failed to detect any of the characteristic bitumen biomarkers, i.e., steranes and triterpanes (10). Interestingly, such humps have also been observed in GC analyses of Pistacia resins from Canaanite jars from Amarna (25). Such humps can also arise through heating.…”
Section: Resultsmentioning
confidence: 82%
“…Such humps can also arise through heating. However, this Pistacia resin does not appear to have been subjected to strong heating, given the absence of the biomarker 28-norolean-17-en-3-one (8) and significant components in the m/z 453 mass chromatogram (25).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies have been performed on wall paintings and ceilings in archaeological palaces and cemeteries dated to Mohammed Ali Era [28] [29] [30]. The blue pigment identified in Sabil-Kuttab Umm Abbas was ultramarine blue which had been previously identified in the Royal family graveyards [28].…”
Section: Discussionmentioning
confidence: 99%